Pemanfaatan Media Sosial Dalam Promosi Dan Pemasaran Usaha Peternak Domba Dan Kambing Di Tenjo - Wiharto, Yudi; Mufti, Mufti; Gata, Grace; Subandi Subandi (Institut Teknologi dan Bisnis Semarang, 2023)
This community service aims to study and implement strategies for using social media in the promotion and marketing of sheep and goat farming businesses in Tenjo. This activity aims to help sheep and goat farmers in Tenjo increase the visibility and profitability of their business through the use of social media as an effective communication and promotional tool. The method used in this community service involves training, mentoring, and implementation in the use of social media such as Instagram as a platform for promotion and marketing of livestock products. Apart from that, training is also carried out regarding the creation of interesting and relevant content and social media management, for promotional effectiveness. The results of this service show that the use of social media has had a positive impact on the business of sheep and goat farmers in Tenjo. They succeeded in increasing the number of customers, sales and brand awareness through more targeted and effective promotional campaigns. In addition, social media is also a tool for building online communities between breeders and customers, increasing engagement and facilitating better communication. In the context of the ever-changing development of information and communication technology, this community service makes a real contribution to increasing the competitiveness and sustainability of sheep and goat farming businesses in Tenjo.